Prussian Blue Films Produced by Pentacyanidoferrate(II) and Their Application as Active Electrochemical Layers (Eur. J. Inorg. Chem. 34/2014). Issue 34 (December 2014) - Morandi Pires, Bruno; Venturinelli Jannuzzi, Sergio Augusto; Barboza Formiga, André Luiz; Alves Bonacin, Juliano
Abstract : The cover picture shows a strategy on how to produce an electrode chemically modified by Prussian Blue films, for which a pentacyanidoferrate(II) complex was used as precursor. The films formed on the electrode have shown good stability and electrocatalytic response for ascorbic acid oxidation. Our results demonstrate the use of Prussian Blue prepared from pentacyanidoferrate(II) as the active layer in electrochemical sensors. Details are discussed in the article by J. A. Bonacin et al. onp. 5812 ff . For more on the story behind the cover research, see theCover Profile .